In vitro oxime-assisted reactivation of paraoxon-inhibited human acetylcholinesterase and butyrylcholinesterase - Musilova, Lucie; Kuca, Kamil; Jung, Young-Sik; Jun, Daniel (Clinical toxicology (Philadelphia, Pa.), 2009)
INTRODUCTION: Organophosphorus pesticides and nerve agents are highly toxic to humans and other living organisms, primarily because of their interaction with enzyme acetylcholinesterase. The aim of our study was to find suitable reactivators of acetylcholinesterase and butyrylcholinesterase and to recommend the most efficacious compounds for the next evaluation as antidotes for intoxication by pesticides. METHODS: Eighteen structurally different oxime reactivators were tested for their in vitro ability to reactivate paraoxon-inhibited human erythrocyte acetylcholinesterase and human plasma butyrylcholinesterase to find out structure-activity relationship within this set of compounds. Their reactivation ability was compared with commercially available acetylcholinesterase reactivators (pralidoxime, methoxime, trimedoxime, obidoxime, and HI-6). RESULTS AND DISCUSSION: The best reactivation ability was achieved with obidoxime, trimedoxime, compounds K027, K075, K203, and K048. We have also tested reactivation of butyrylcholinesterase with the aim to recommend an efficient reactivator, able to perform a "pseudo catalytic" bioscavenger with butyrylcholinesterase, which is developed as new antidote of organophosphate poisonings. Such combination could allow an enhancement of prophylactic and therapeutic efficiency of administered enzyme. Compounds K117, K269, K075, and trimedoxime were found to be the most potent reactivators of inhibited butyrylcholinesterase. CONCLUSIONS: In this work, we have evaluated only reactivation of paraoxon-inhibited cholinesterases. To get better understanding of this problem, a larger number of organophosphorus inhibitors should be used.
Keywords: Cholinesterase Inhibitors; kvantitativní vztahy mezi strukturou a aktivitou; antidota; molekulární struktura; Molecular Structure; Paraoxon; acetylcholinesterasa; Cholinesterase Reactivators; kultivované buňky; Antidotes; lidé; Humans; reaktivátory cholinesterasy; erytrocyty; Erythrocytes; Cells, Cultured; Quantitative Structure-Activity Relationship; Acetylcholinesterase; cholinesterasové inhibitory; paraoxon